2019
DOI: 10.1007/s10047-018-1085-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen delivery to the blood stream by the dialysis fluid during continuous renal replacement therapy ex vivo

Abstract: Continuous renal replacement therapy (CRRT) maintains a balance in body water and electrolytes. CRRT supplies a higher quantity of fluid than intravenous fluid therapy along with simultaneous fluid withdrawal. We hypothesized that use of a high-oxygen-containing solution for high-volume fluid exchange would improve oxygenation in the blood during CRRT. To start with, we prepared a solution containing high oxygen. The objective of this study was to determine if this solution would increase the partial pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…14 In this study, the CRRT was used in the treatment of patients with AKI. Our results showed that the total effective rate and survival rate after six months in the observation group were higher than those in the control Huihui Hou et al 17 In addition, the levels of serum K + , Cland Na + in the observation group after the treatment were also lower than those in the control group (P<0.05), suggesting that the CRRT can also promote the recovery of serum electrolytes and fluid balance in patients with AKI, in agreement with the study of Tangy et al 18 CRRT simulates the process of removing solute and water from the kidney by simulating glomerular filtration. It removes solutes with molecular weight less than 50000 in the form of convection.…”
Section: Discussionsupporting
confidence: 84%
“…14 In this study, the CRRT was used in the treatment of patients with AKI. Our results showed that the total effective rate and survival rate after six months in the observation group were higher than those in the control Huihui Hou et al 17 In addition, the levels of serum K + , Cland Na + in the observation group after the treatment were also lower than those in the control group (P<0.05), suggesting that the CRRT can also promote the recovery of serum electrolytes and fluid balance in patients with AKI, in agreement with the study of Tangy et al 18 CRRT simulates the process of removing solute and water from the kidney by simulating glomerular filtration. It removes solutes with molecular weight less than 50000 in the form of convection.…”
Section: Discussionsupporting
confidence: 84%
“…In resource-poor environments where ECMO capabilities are not available, it has been proposed to use hollow fibre membrane dialysers for respiratory support as dialysis is a widely used technique, with existing clinical approval and a lower resource cost (Rubin, Stacey, Matambo, Vale, et al, 2020). Dialysers are used for haemodialysis therapy and continuous renal replacement therapy (CRRT) where they replace kidney function by filtering small and medium toxins and managing electrolyte and acid balances in the body (Tange & Yoshitake, 2019;ter Beek et al, 2020).…”
Section: Hollow Fiber Membrane Dialysers (Hfmd)mentioning
confidence: 99%
“…The differences are in the membrane type, flow rate, and counter-current flow. HFMD commonly uses a polysulfone membrane that is more permeable than membranes used in ECMO as it is required to exchange not just gas but larger toxins and fluids as well (Tange & Yoshitake, 2019;ter Beek et al, 2020). Dialyser cartridges are also smaller than ECMO resulting in a lower blood flow which means a single cartridge set-up is not capable of providing full oxygenation of blood (Rubin, Stacey, Matambo, Vale, et al, 2020;Sidebotham et al, 2012).…”
Section: Hollow Fiber Membrane Dialysers (Hfmd)mentioning
confidence: 99%
See 2 more Smart Citations